The Relationship between Self-Efficacy and Family Social Support with the Psychological Well-Being of High School Students - Prawita, Citra Bella; Nurfarhanah, Nurfarhanah; Neviyarni, Neviyarni; Hariko, Rezki (Universitas Ahmad Dahlan, 2024)
The psychological well-being felt by teenagers makes teenagers have more positive emotions within themselves and can foster a sense of life satisfaction and happiness, thereby reducing negative behavior and reducing feelings of depression. This research aims to determine the relationship between self-efficacy and family social support on students' psychological well-being. This research is correlational research. The sample of this research consisted of 252 students. The research results show that self-efficacy and family social support simultaneously (together) have a significant relationship with students' psychological well-being. This finding was obtained based on a series of data analyzes that there is a strong relationship between self-efficacy and family social support on psychological well-being of 56.3%, then the variables of self-efficacy and family social support can explain students' psychological well-being of 31.7%.